(untitled) (مجلة أبحاث قانونية, 2024)
Conflict between laws are resolved by the rules of attribution established by Germany jurist Savigny, according to which: Analysis of the relationship,its focus is in a specific society, and then the laws of that society are applied to that relationship, In light of globalization, some jurists saw the need to exclude thisclassical methodin favor of other methods that are more capable of keeping pace with the development of international trade in its modern world. This represents a deliberate denial of Ssvigniesm.